(untitled) (Global Journal of Science Frontier Research, 2023)
The main objective of this research work, is to make a critical analysis of the application, of coefficient α, since it was proposed by Coriolis in 1836. According to the international literature and the internet, widely consulted by the author of this work, the Coriolis coefficient for the correction of the velocity head (kinetic energy), is affirmed and recognized in the conduction fluid flows, because when considering the average velocity (ratio between discharge and velocity), as the average of the actual distribution of velocities occurring in the cross section, an error occurs, due to the non-uniform distribution of velocities. The author of this technical article, in performing a thorough and detailed analysis of the deduction of the coefficient , the continuity equations, Bernoulli (laws of conservation of mass and energy, respectively, applied to the flow of fluids), as well as the general formulas of fluid resistance, Weisbach-Darcy, etc. has come to the conclusion that while the coefficient of Coriolis actually exists, the way in which it has been used is not the right one.